2004
DOI: 10.1021/jo049368v
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Dendrimers with Allyl Ether End-Groups Using the Ring-Closing Metathesis Reaction

Abstract: A third generation Frechet-type dendrimer containing 24 allyl ether end-groups was synthesized, cross-linked using the ring-closing metathesis (RCM) reaction, and the core was removed hydrolytically without significant fragmentation. The results are analogous to those previously reported for homoallyl ether dendrimers (Wendland, M. S.; Zimmerman, S. C. J. Am. Chem. Soc. 1999, 121, 1389-1390) suggesting that the less readily available homoallyl ether dendrimers can be replaced by their allyl ethers analogues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…The spectral data of 3 was compared with that already published. 5,12 1,3,5-Tris-[3,5-bis(allyloxy)benzyloxy]benzene (6). To a round bottom flask containing K2CO3 (1.53 g, 11.1 mmol) in DMF:THF (60:12 mL) as solvent, under nitrogen atmosphere, was added phloroglucinol 5 (0.20 g, 1.23 mmol) and the mixture was heated at 70 °C followed by addition of 3,5-diallyloxybenzyl chloride 2 (0.88 g, 3.69 mmol).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral data of 3 was compared with that already published. 5,12 1,3,5-Tris-[3,5-bis(allyloxy)benzyloxy]benzene (6). To a round bottom flask containing K2CO3 (1.53 g, 11.1 mmol) in DMF:THF (60:12 mL) as solvent, under nitrogen atmosphere, was added phloroglucinol 5 (0.20 g, 1.23 mmol) and the mixture was heated at 70 °C followed by addition of 3,5-diallyloxybenzyl chloride 2 (0.88 g, 3.69 mmol).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Although in general the yields are good, when the reaction between the dendron of the second generation and 1,3,5-tris-(4-hydroxyphenyl)benzene (THPB) as core is carried out, the yield falls to 53%. Motivated by potential applications of poly(aryl ether) dendrimers with allyl ether end groups such as preparation of cross-linked dendrimeric materials via ring closing metathesis reactions, [2][3][4][5] the advantage of selective removal of the protecting groups with Pd catalysts to provide peripheral hydroxyl groups that can be functionalized with hydrophobic chains to form new supramolecular polymers, 6 but mainly because these groups are active for hydrosilylation reactions to obtain metallodendrimers with high-boron-content that can be applied in boron neutron capture therapy (BNCT), 7 we have continued working on the synthesis of dendrimers with allyl ether terminal groups.…”
Section: Introductionmentioning
confidence: 99%
“…Cross metathesis reaction in polyolefin molecules is often condemned by the possibility of intramolecular ring closing metathesis (RCM) or by the intermolecular cross‐linking . However, in the Astruc group we demonstrated that it is possible to use olefin cross metathesis to efficiently functionalize polyolefin dendrimers using the Grubbs catalyst 2 nd generation and acrylate derivatives (olefins bearing electron withdrawing groups) .…”
Section: Reactions Used For Dendrimers' Synthesis and Functionalizationmentioning
confidence: 99%
“…Cross metathesis reaction in polyolefi n molecules is often condemned by the possibility of intramolecular ring closing metathesis (RCM) or by the intermolecular cross-linking. [ 27 ] dendrimers up until generation nine, which possesses approximately 177 000 terminal groups ( vide infra , Section 3). [ 13a , 24 ] In the Astruc group, we further developed a one-pot synthetic strategy that consisted in hydrosilylation of a nonaallyl dendritic core using H(CH 3 ) 2 SiCl followed by reaction with a phenolate dendronic brick bearing three allyl groups.…”
Section: Reactions Used For Dendrimers' Synthesis and Functionalizationmentioning
confidence: 99%
“…These special structure and properties are drawing more and more attentions on HBPs in the fields of catalysts, [1][2][3] organic nanoparticles, [4][5][6] ultra thin films, [7,8] etc. Concerning the synthesis efficiency, one of the reasonable exploration trends is to fabricate larger-matrix materials with novel properties using HBPs (especially for those in sticky states).…”
Section: Introductionmentioning
confidence: 99%